Intramedullary Tibial Nailing Reduces the Attachment Area and Ultimate Load of the Anterior Medial Meniscal Root: A Potential Explanation for Anterior Knee Pain in Female Patients and Smaller Patients. (July 2015) - LaPrade, Matthew D.; LaPrade, Christopher M.; Hamming, Mark G.; Ellman, Michael B.; Turnbull, Travis Lee; Rasmussen, Matthew T.; Wijdicks, Coen A.; LaPrade, Robert F.
Background: Intramedullary (IM) nailing is the treatment of choice among orthopaedic surgeons for tibial shaft fractures. However, because of the close proximity of the nail's insertion site to the anterior medial (AM) meniscal root on the tibial plateau, there is increased risk of iatrogenic injury to the meniscal root during nailing. Purpose: To quantify the area of the AM meniscal root footprint damaged by IM tibial reaming and determine its subsequent effects on the ultimate failure load in female versus male knees. Study Design: Controlled laboratory study. Methods: Twelve matched pairs (6 male and 6 female pairs; average age, 50.2 years) of human cadaveric knees were randomly assigned to native and reamed groups. In the reamed group, knees were reamed within the "safe zone" according to current guidelines for IM tibial nail insertion (3 mm lateral to the center of the tibial tubercle and adjacent to the anterior margin of the tibial plateau). The attachment areas and ultimate failure load were quantified and compared with paired knees in the native group. Results: Intra-articular reaming within the "safe zone" for IM tibial nail insertion did not significantly decrease the AM root attachment area or ultimate failure load in male specimens, as only 2 of the 6 knees were damaged by reaming. In contrast, all 6 of the AM roots in the female knees were damaged by reaming, and on average, reaming decreased the female AM root attachment area by 19% and significantly decreased ultimate failure load by 37% ( P = .028). There was a strong negative correlation ( R 2 = 0.77) between reamed tunnel–AM root overlap area and medial-lateral width in female but not in male knees. Conclusion: Standard reaming for an IM tibial nail induced significant damage to the AM meniscal root in smaller, female specimens, whereas larger, male specimens were not affected. Clinical Relevance: These findings may suggest that improvements in current guidelines and surgical techniques are warranted to prevent iatrogenic injury to the AM meniscal root during intramedullary reaming for tibial shaft fractures in females and in smaller patients.